2001
DOI: 10.1093/rheumatology/40.10.1146
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte phenotype and cell survival are regulated by culture conditions and by specific cytokines through the expression of Sox‐9 transcription factor

Abstract: The results suggest that the effects of cartilage anabolic and catabolic cytokines IGF-1 and IL-1alpha on the expression of the chondrocyte phenotype are mediated by Sox-9. As Sox-9 appears to be essential for matrix production, the potent effect of IL-1alpha in suppressing Sox-9 expression may limit the ability of cartilage to repair during inflammatory joint diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
65
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 66 publications
4
65
0
Order By: Relevance
“…Similar results were observed with both ITS and Igf1, which is one of the most potent growth factors promoting cartilage maintenance and regeneration (35)(36)(37). ␤-Catenin signaling also enhances post-natal chondrocyte proliferation and is required for the maintenance of articular cartilage (20, 38 -40).…”
Section: Discussionsupporting
confidence: 59%
“…Similar results were observed with both ITS and Igf1, which is one of the most potent growth factors promoting cartilage maintenance and regeneration (35)(36)(37). ␤-Catenin signaling also enhances post-natal chondrocyte proliferation and is required for the maintenance of articular cartilage (20, 38 -40).…”
Section: Discussionsupporting
confidence: 59%
“…Since the Cys 78 -Arg mutation in the putative IGFBP domain of WISP3 partially abolishes WISP3 function in chondrocytes, it is conceivable that WISP3 may act, in part, by augmenting the effects of IGFs. IGF-1-mediated up-regulation of cartilage ECM synthesis has already been reported by investigators at several laboratories (30)(31)(32). In addition, preliminary experimental results have demonstrated that an anti-IGF-1 neutralizing antibody partially blocks WISP3-mediated up-regulation of COL2A1 mRNA in C-28/I2 cells.…”
Section: Discussionmentioning
confidence: 54%
“…12 The expression of sox9 in primitive mesenchymal cells induced chondrocytic phenotype: for example, the expression of cartilage-specific matrix molecules such as type II collagen and aggrecan. 19,20 In these cases, the expression of sox9 was more diffuse in the nuclei of metaplastic cells than in carcinomatous cells. S-100 protein expression in matrix-producing carcinoma, especially in metaplastic cells, is well known 2 and is frequently seen in chondrocytes and chondrocytic tumors.…”
Section: Discussionmentioning
confidence: 87%